2023
DOI: 10.3390/molecules28207165
|View full text |Cite
|
Sign up to set email alerts
|

Peptides as Therapeutic Agents: Challenges and Opportunities in the Green Transition Era

Giacomo Rossino,
Emanuela Marchese,
Giovanni Galli
et al.

Abstract: Peptides are at the cutting edge of contemporary research for new potent, selective, and safe therapeutical agents. Their rise has reshaped the pharmaceutical landscape, providing solutions to challenges that traditional small molecules often cannot address. A wide variety of natural and modified peptides have been obtained and studied, and many others are advancing in clinical trials, covering multiple therapeutic areas. As the demand for peptide-based therapies grows, so does the need for sustainable and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 155 publications
(214 reference statements)
0
11
0
Order By: Relevance
“…18 The present study found that the addition of a mixture of these inhibitory compounds significantly mitigated αCT11 degradation after 30 min incubation at both 22 and 37 °C and after 60 min incubation at 22 °C (Figure 5), leading to an overall increase of half-life to about 30−50 min at 37 °C, which could significantly accelerate therapeutic efficacy in protein or peptide-based therapies. 63 However, the cocktail of inhibitors used in the present study is unlikely to be used for clinical management because of the likelihood of side effects from some, or all, of the components in such mixtures. For this reason, other strategies must be explored to reach the same goal of increasing the stability and half-life of therapeutic peptides.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 The present study found that the addition of a mixture of these inhibitory compounds significantly mitigated αCT11 degradation after 30 min incubation at both 22 and 37 °C and after 60 min incubation at 22 °C (Figure 5), leading to an overall increase of half-life to about 30−50 min at 37 °C, which could significantly accelerate therapeutic efficacy in protein or peptide-based therapies. 63 However, the cocktail of inhibitors used in the present study is unlikely to be used for clinical management because of the likelihood of side effects from some, or all, of the components in such mixtures. For this reason, other strategies must be explored to reach the same goal of increasing the stability and half-life of therapeutic peptides.…”
Section: ■ Discussionmentioning
confidence: 99%
“…As such, antagonists have the potential to increase the half-life of therapeutic peptides undergoing clinical testing. , In lab research, PTase/PPTase inhibitor cocktails are commonly used together with cell lysis reagents to prevent degradation of extracted proteins for various protein analyses, such as Western blot . The present study found that the addition of a mixture of these inhibitory compounds significantly mitigated αCT11 degradation after 30 min incubation at both 22 and 37 °C and after 60 min incubation at 22 °C (Figure ), leading to an overall increase of half-life to about 30–50 min at 37 °C, which could significantly accelerate therapeutic efficacy in protein or peptide-based therapies …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While oromucosal administration using medicated candies is still a relatively novel strategy and has yet to be fully established for other suitable candidate peptide or non-peptide drugs, it may open up future possible avenues for administering either acute or long-term medication to individuals where other routes are less well-tolerated. In recent years for example, there has been a considerable growth in the number of peptide-based therapeutic drugs, with currently > 80 having been approved for use [ 61 ]. Peptide drugs offer several advantages over small molecules, including a heightened target specificity and potency and reduced side effects, although few have been developed for oromucosal administration.…”
Section: Discussion and Future Potential Developments And Applicationsmentioning
confidence: 99%
“…Peptide drugs offer several advantages over small molecules, including a heightened target specificity and potency and reduced side effects, although few have been developed for oromucosal administration. A full consideration of the current numerous peptide-based drugs, other than oxytocin, is beyond the scope of the current review and has been covered in another publication (see [ 61 ]). As outlined in Figure 1 , the two obvious potential limitations for the oromucosal administration of peptide-based drugs as opposed to small molecules are that high molecular weights may result in poor penetration through the oral mucosae and that they are often metabolized too rapidly.…”
Section: Discussion and Future Potential Developments And Applicationsmentioning
confidence: 99%